Benign Oral Cavity and Oropharyngeal Lesions: A Histopathological Review and Their Relationship to HPV Infection - Afiati; Khoirul Anam (CV. Inara, 2026)
Background: Human Papillomavirus (HPV) is one of the causes of benign lesions in the oral cavity and oropharynx. The most common lesions include squamous cell papilloma, condyloma acuminatum, verruca vulgaris, and multifocal epithelial hyperplasia (MFEH). Although benign, these four lesions have overlapping clinical and histopathological characteristics, often making diagnosis difficult. The purpose of this literature review is to review the clinical characteristics, histopathology, differential diagnosis, management, and prognosis of benign lesions of the oral cavity and oropharynx associated with HPV infection. Methods: This article was compiled using a narrative literature review method. The literature search was conducted through PubMed, Google Scholar, and ScienceDirect using keywords related to HPV and benign lesions of the oral cavity. Literature published in Indonesian and English between 2017 and 2025 was selected based on relevance to the anatomy, histology, epidemiology, etiology, clinical manifestations, macroscopic and microscopic features, differential diagnosis, management, and prognosis of benign lesions of the oral cavity and oropharynx associated with HPV. Results: Benign lesions of the oral cavity and oropharynx associated with HPV consist of squamous cell papilloma, condyloma acuminatum, verruca vulgaris, and MFEH. Most lesions are associated with low-risk HPV infection, especially types 6 and 11, with a predilection for the labial mucosa, tongue, buccal mucosa, and palate. The clinical presentation of lesions associated with HPV is generally an exophytic growth with a papillary or verrucous surface. Histopathologically, all lesions showed squamous epithelial proliferation accompanied by koilocytes as a marker of HPV cytopathic effects, while mitosoid bodies are a characteristic feature and are more frequently found in MFEH. Diagnosis is established through correlation between history taking, clinical examination, and histopathological evaluation to differentiate benign lesions from potentially malignant lesions. Simple excision is the mainstay of therapy with a generally good prognosis, although condyloma acuminatum has a tendency to recur. Conclusion: Diagnosis of benign lesions of the oral cavity and oropharynx associated with HPV requires integration of clinical characteristics, histopathology, and, if necessary, molecular examination. Understanding the differences in the characteristics of each lesion is important to improve diagnostic accuracy, determine appropriate management, and prevent misdiagnosis of malignant lesions.